The Characteristics of Demand Rates in Inventory Routing Problem - Harahap, Afif Zuhri Muhammad Khodri; Nursal, Ahmad Taufik; Sahlan, Khairulnizam; Sobry, Suheil Che (Advances in Social Sciences Research Journal, 2023)
In today's business landscape, demand variability plays a crucial role in determining the success of companies across various industries. This article explores the concept of demand variability, encompassing both deterministic and stochastic demand patterns. We delve into the differences between these demand types and their implications for businesses. The article emphasizes the significance of accurate demand forecasting and its role in strategic decision-making. Deterministic demand, characterized by predictable patterns, allows businesses to forecast with certainty. On the other hand, stochastic demand introduces uncertainty, requiring statistical methods and probability theory for estimation and management. Furthermore, we explore the distinction between stochastic stationary demand and stochastic nonstationary demand. While the former maintains consistent statistical properties over time, the latter experiences fluctuations in its characteristics due to external factors. We highlight the challenges faced by businesses in forecasting and managing nonstationary demand and the need for adaptive forecasting methods. To successfully navigate today's dynamic market, companies must embrace advanced analytics and data-driven approaches. By leveraging historical data, statistical models, and forecasting techniques, businesses can gain valuable insights into demand patterns, optimize inventory management, and make informed strategic decisions. Ultimately, understanding and managing demand variability is paramount for businesses seeking to improve customer satisfaction, optimize operations, and enhance their competitive advantage. This article aims to provide a comprehensive understanding of demand variability and equip readers with insights and strategies to tackle the challenges posed by an ever-changing market landscape.